THE EFFECTS OF MULTIPLE INTELLIGENT (IQ, EQ, AND AQ) ON EMPLOYEE PERFORMANCE: A CASE OF ABC AUTOMOTIVE CO., LTD. - Soysub, Angkana; Jarinto, Krit (RMUTT GLOBAL BUSINESS ACCOUNTING AND FINANCE REVIEW, 2018)
The objective of this independent study was to study multiple intelligence including (intelligence quotient, emotional quotient and adversity quotient) that are related to job performance of employees in ABC Company located in Amata City Industrial Estate and to use the results of the study as a guideline for human resource department to develop, train and improve work ability of employees. The respondents consisted of 210 employees who worked in Automotive Company in Amata City Industrial Estate Rayong Province. The questionnaires were used to collect the data. The data analysis employed frequency, percentage, mean, standard deviation and multiple regression model. The analyzed results showed that the intelligence quotient and emotional quotient in terms of empathy and self-management had an effect on employee performance at the significance of 0.00, 0.03 and 0.00, respectively.